Structural chemistry and magnetic properties of La2LiRuO6 - Battle, P; Grey, C; Hervieu, M; Martin, C; Moore, C; Paik, Y (2003)
A combination of magnetometry, electron microscopy, neutron diffraction and 7Li MASNMR spectroscopy has been used to determine that La 2LiRuO6 has a monoclinic perovskite-related structure (space group P21/n, a=5.5555(2), b=5.5977(2), c=7.8454(3)Å, β=90.020(5)° at 300K) with a 1:1 ordered arrangement of Li+ and Ru5+ cations occupying the six-coordinate sites. The compound is antiferromagnetic (type I) below 30K with an ordered magnetic moment of 2.2(2)μB per Ru. The magnetic properties of this phase are compared with those of Sr3LiRuO6 and Ca 3LiRuO6. © 2003 Elsevier Inc. All rights reserved.